2023
DOI: 10.1108/jstp-08-2022-0163
|View full text |Cite
|
Sign up to set email alerts
|

“Turning role conflict into performance”: assessing the moderating role of self-monitoring, manager trust and manager identification

Abstract: PurposeThis study examines the contextual variables that can curb the negative effects of role conflict on job satisfaction and enhance the positive effect of job satisfaction on creativity and service performance. More specifically, adopting the job demands-resources theory, the authors explore the interactive effect of frontline employee (FLE) self-monitoring and FLE-manager trust on the relationship between role conflict and job satisfaction. Extending this line of inquiry, the authors adopt social identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 121 publications
0
0
0
Order By: Relevance
“…We contend that capability control can be used to provide salespeople with feedback on the knowledge and skills required to provide excellent customer service (Fang et al , 2005) and Capability information is used to improve salespeople’s sales skills and capabilities (Epler et al , 2023; Kalra et al , 2023a, 2023b) so that they can skillfully seek, process and understand customer feedback (Carver and Scheier, 1982). Salespeople articulate their goals by gathering and interpreting role information from customers under their capability control (Challagalla and Shervani, 1996).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…We contend that capability control can be used to provide salespeople with feedback on the knowledge and skills required to provide excellent customer service (Fang et al , 2005) and Capability information is used to improve salespeople’s sales skills and capabilities (Epler et al , 2023; Kalra et al , 2023a, 2023b) so that they can skillfully seek, process and understand customer feedback (Carver and Scheier, 1982). Salespeople articulate their goals by gathering and interpreting role information from customers under their capability control (Challagalla and Shervani, 1996).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…However, in a common conclusion of role stress research, role stress is associated with negative value states, leading to tension and low job satisfaction (Jackson and Schuler, 1985; Kim et al , 2009; Schwepker and Hartline, 2005). For example, according to the COR theory, interrole conflict can result in a loss of resources or an imbalance between resources and needs, leading to negative psychological outcomes that include dissatisfaction with the job, depression, anxiety, burnout, physiological tension (Bagozzi and Verbeke, 2020; Jex, 1998; Kahn et al , 1964; Kalra et al , 2023a, 2023b; Talukder, 2019). In addition, Kohli (1985) demonstrated that greater role clarity increases job satisfaction.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations